2012
DOI: 10.1111/j.1365-2672.2012.05355.x
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of anti-microbial peptides with enhanced activity and low cytotoxicity based on the structure of the arginine/histidine-rich peptide, chensinin-1

Abstract: Aims: To understand the structure-activity relationship of chensinin-1, a antimicrobial peptide (AMP) with an unusual structure, and to develop novel AMPs as therapeutic agents. Methods and Results: A series of chensinin-1 analogues were designed and synthesized by one to three replacement of glycines with leucines at the hydrophilic face of chensinin-1 or rearrangement of some of the residues in its sequence. Circular dichroism spectroscopy showed that the analogues adopted a-helical-type conformations in 50%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Hodges and co-workers [6] also reports similar results for analogs of a 26-residue ␣-helical antimicrobial peptide. It is accepted that an increase in hydrophobicity for ␣-helix antimicrobial peptides results in an increase in both antimicrobial and hemolytic activities [14,22]. In our study we modified the analogs of BmKn1 by systematic substitution on positions 5 and 9 with alanine, valine and leucine, thereby increasing the hydrophobicity.…”
Section: Discussionmentioning
confidence: 97%
“…Hodges and co-workers [6] also reports similar results for analogs of a 26-residue ␣-helical antimicrobial peptide. It is accepted that an increase in hydrophobicity for ␣-helix antimicrobial peptides results in an increase in both antimicrobial and hemolytic activities [14,22]. In our study we modified the analogs of BmKn1 by systematic substitution on positions 5 and 9 with alanine, valine and leucine, thereby increasing the hydrophobicity.…”
Section: Discussionmentioning
confidence: 97%
“…Chensinin-1 is a histidine rich peptide produced by the frog, Rana chensinensis and recent studies showed that low pH enhanced the positive charge of the peptide [31] and thereby, its ability to kill Gram-positive bacteria, such as Bacillus cereus [32]. This antibacterial activity appeared to involve the adoption of an extended structure, similar to that of other AMPs that are rich in specific residues [101,102], which induced lysis of the B. cereus membrane [32].…”
Section: An Overview Of Ph Dependent Peptides and Proteins With Anmentioning
confidence: 99%
“…In the present study, chensinin-1b was designed and synthesised by the substitution of three Trp residues for Gly residues on the hydrophobic side, based on the amino acid sequence of chensinin-1a. CD spectroscopy showed that the a-helical content of chensinin-1b increased sharply from 4.45% in water to 28.06% in 50% TFE solution, and still exhibited a much lower a-helical content than that of Leu-substituted analogues, with 66.3% a-helix content [20]. By changing the primary structure, and because of the special characteristics of Trp residues, the antimicrobial activity of chensinin-1b has been greatly improved, especially against Gramnegative bacteria.…”
Section: Discussionmentioning
confidence: 90%
“…Importantly, chensinin-1 displays potent antimicrobial activity against Gram-positive bacteria, but has no haemolytic activity, and thus has potential as a novel antibiotic. In our previous study [20], a designed chensinin-1 analogue, chesinin-1a, in which its sequence was rearranged by adjusting its hydrophilic/polar residues on one face and its hydrophobic/nonpolar residues on the opposite face, is shown in the helical diagrams in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%